Factors associated with the discontinuation of modern contraceptive methods among lactating women in nine West African high-fertility countries: findings of the most recent demographic and health surveys - Abou Coulibaly; Adama Baguiya; Denise Kpebo; Augustin Zango; Halima Tougri; Franck Garanet; Seni Kouanda (Archives of Public Health)
Abstract Introduction Contraception discontinuation is a concern, especially if it occurs in breastfeeding women, thereby exposing them to a high risk of close and unwanted pregnancies. Our study aimed to measure the prevalence and identify the individual and community-level factors associated with the discontinuation of modern contraceptives among breastfeeding women. Methods This was a secondary analysis of retrospective data of the most recent Demographic and Health Surveys (DHS) data from nine high-fertility rate countries, conducted mostly between 2018–2021. We reported weighted frequencies of modern contraceptives discontinuation (binary variable, coded 1 and 0). The independent variables included individual-level variables, including sociodemographic characteristics, female reproduction and family planning history, the women and their households exposure to media, and community-level ones such as place of residence (urban and rural) and country. Multilevel-modified Poisson regression was used to identify associated factors at the 5% threshold. Results The overall prevalence of modern contraceptives discontinuation was 13.1% among 5,599 lactating mothers, with wide variations between countries (prevalence ranging from 8.2% in Sierra Leone to 33.6% in Guinea). Women were more likely to discontinue contraception if they were the head of the household (adjusted prevalence ratio (aPR) = 1.71; 95% CI [1.17–2.50]; p = 0.006). In addition, compared to implant users, women using pills (aPR = 3.06; 95% CI [2.24–4.16]; p < 0.001), those using injectables (aPR = 2.80; 95% CI [2.16–3.62]; p < 0.001), and women whose partners used condoms (aPR = 2.30; 95% CI [1.47–3.59]; p < 0.001) were more likely to discontinue contraception. Moreover, women who were not sexually active (aPR = 2.11; 95% CI [1.75–2.54]; p < 0.001) and those who wanted children within two subsequent years (aPR = 1.84; 95% CI [1.36–2.48]; p < 0.001) were more likely to discontinue contraception. Finally, method discontinuation varied by country, with women in Gambia, Guinea, Mauritania, and Mali more likely to discontinue a modern contraceptive method than those living in Burkina Faso. Conclusion To improve the retention of women using contraceptive, high-fertility rate countries need to focus on contraceptive education, communication about side effects, dissemination of family planning messages through the media, and regular monitoring of women taking contraceptives.